2022
DOI: 10.33448/rsd-v11i16.38434
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania spp. in canine serum fixed in card

Abstract: Visceral leishmaniasis is a serious zoonosis, and its molecular diagnosis is an important strategy. The detection of Leishmania spp. DNA from biological samples fixed in cards could solve problems related to the collect and transport of biological samples. The purpose of this study was to detect Leishmania spp. by PCR, using canine serum fixed in cards (CSFC). For evaluation, the PCR with DNA extracted from CSFC (PCR/card) was compared to the PCR with DNA from the same serum extracted using the Qiagen kit (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Our study used a simplified DNA extraction protocol previously shown to liquefy the sample and to facilitate the retention of the DNA in the FTA card, which is essential for sample storage and transport [15]. FTA cards have already been used in studies with sputum, blood, and saliva samples [14,24,25,26]. Efficient nucleic acid extraction is essential for the successful diagnosis of TB by qPCR and for effectively contributing to disease control [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our study used a simplified DNA extraction protocol previously shown to liquefy the sample and to facilitate the retention of the DNA in the FTA card, which is essential for sample storage and transport [15]. FTA cards have already been used in studies with sputum, blood, and saliva samples [14,24,25,26]. Efficient nucleic acid extraction is essential for the successful diagnosis of TB by qPCR and for effectively contributing to disease control [27].…”
Section: Discussionmentioning
confidence: 99%